2013
DOI: 10.1016/j.otsr.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of distal humerus fractures in patients above 65 years of age treated by plate fixation

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 25 publications
2
29
2
Order By: Relevance
“…The surgical revision rate in elbow surgery is quite high compared to other anatomical regions [ 15 18 ], which is supported by the findings in this study. In 8 of 36 patients (22.2 %) the index operation was performed due to implant failure or secondary dislocation of a previous surgery.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The surgical revision rate in elbow surgery is quite high compared to other anatomical regions [ 15 18 ], which is supported by the findings in this study. In 8 of 36 patients (22.2 %) the index operation was performed due to implant failure or secondary dislocation of a previous surgery.…”
Section: Discussionsupporting
confidence: 90%
“…Intra-articular fractures of the elbow are prone to revision surgery in the case of secondary dislocation, intra-articular position of screws or remaining gaps after primary surgical treatment. In the treatment of elbow fractures a satisfactory outcome relies on anatomical reconstruction of the joint surface and proper implant placement [ 15 19 ]. Based on this background, intraoperative 3D imaging may be beneficial in the treatment of elbow fractures to improve outcome and prevent revision surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise an operative treatment is recommended. The development of locking compressions plates improved the primary stability of fracture fixation [3] especially in patients with poor bone mineral quality [4][5][6]. Open reduction and internal fixation (ORIF) with a double locking plate osteosynthesis became the gold standard for the fixation of intra-articular distal humerus fractures, while the positioning and configuration of the plates is still discussed [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have compared the functional outcome of TEA versus ORIF and found both to be favorable. 8 , 9 , 11 , 13 , 17 22 …”
Section: Discussionmentioning
confidence: 99%